Tradisi Hataman Qur’an di Madura: Resiliensi dan Agensi Nalar Moderasi Islam - Fathurrosyid Fathurrosyid; Abdul Hakim; Moh. Muhyan Nafis (SUHUF, 2022)
The new media revolution has knocked down religious institutions. Digitization of manuscripts, apart from the positive effect being interactive, is also in the form of impersonalization of the negative effects, resulting in emergency breaking conditions for children to recite the Qur'an. However, in the midst of the siege of the revolution, four districts in Madura demonstrated the resilience of the Hataman Qur'an tradition and became agents of Islamic moderation reasoning. This research will answer two main issues; First, the argument for the resilience of the Hataman Qur'an tradition in Madura. Second, the model of Islamic moderation reasoning agency in the Hataman Qur'an tradition in Madura. This research is a field research work that focuses on kiai langgar, santri, guardians of santri and the community as the subject. While the object is the Hataman Qur'an tradition in Madura. Using the theory of resilience and moderation reasoning, as well as a critical discourse analysis knife, this paper produces conclusions; First, the resilience of the Hataman Qur'an tradition in Madura is due to three factors (a) social capital, the capability of the Madurese who uphold social values ​​(b) community competencies, the character of the Madurese who like to work together and collaborate with others and (c) social connections, the implementation of Hataman Qur'an using a network with family as social bonding; balater and skipper as social bridging and kiai or politician as social lingking. Second, the reasoning agency of Islamic moderation in the Hataman Qur'an in Madura can be found in the implementation of Aparloh, Entar Nyalase and Jheren Kencak.